A new genus and species from Brazil of the resurrected family Macromaxillocarididae Alvarez, Iliffe & Villalobos, 2006 and a worldwide list of Stenopodidea (Decapoda). Issue 6 (19th September 2020) - Bochini, Gabriel L; Cunha, Andressa M; Terossi, Mariana; Almeida, Alexandre O
Abstract: A new genus and species, Chicosciencea pernambucensis gen. nov., sp. nov ., is described from two localities along the coast of Pernambuco state, northeastern Brazil. Considering the unresolved situation of the families of Stenopodidea in previous studies, the position of this new genus is discussed based on morphological, molecular (16S mtDNA), and ecological data. The morphological analysis revealed that Chicosciencea gen. nov . differs from all stenopodidean genera by a combination of characters. The inferred molecular phylogeny recovered a monophyletic group including Chicosciencea gen. nov ., Macromaxillocaris Alvarez, Iliffe & Villalobos, 2006, and Microprosthema Stimpson, 1860, which comprise free-living (i.e., not-sponge associated), shallow-water species. Based on this monophyletic group and on their morphological and ecological similarities, we herein formally propose the resurrection of Macromaxillocarididae Alvarez, Iliffe & Villalobos, 2006 to include those genera. We also provide an updated world list of Stenopodidea. With the description of Chicosciencea gen. nov ., the infraorder Stenopodidea now comprises 13 genera and 92 species.